The Use Of Flashcards In Teaching Vocabulary At Fourth Grade Students Of SDN Sukosari 02 Dagangan Madiun. - Brigitta Septarini Rahmasari (Jurnal Pendidikan Edutama, 2016)
The Use of Flashcards in Teaching Vocabulary at Fourth Grade Students of SDN Sukosari 02 Dagangan Madiun. In this reserach, the researcher formulates three problems. Those are â€œWhat are the procedures of flashcards and what are strengths and weaknesses of flashcards in teaching vocabulary for fourth grade students of SDN Sukosari 02 Dagangan Madiun?â€. In this research, the researcher uses descriptive research. The sample of the research is the fourth grade students of SDN Sukosari 02 which consists of 26 students. To collect the data, the researcher uses observation and test. Then, to analyze the data the researcher uses reduction, display and conclusion. The results of the research in application of flashcards in teaching vocabulary for students of fourth grade are the studentsâ€™ average score after the implementation of flashcards is 8.15 and the studentsâ€™ average score before the implementation of flashcards is 7.40. So, it is analytically concluded that the implementation of flashcards in teaching vocabulary of fourth grade of SDN Sukosari 02 Dagangan is effective. The strengths of flashcards in teaching vocabulary are flashcards gives some contribution for the studentsâ€™ competence and achievement, there is almost without weaknesses within the use of flashcards in teaching vocabulary for elementary school students.Key words: Teaching Vocabulary, Flashcard.